Adaptation and Psychometric Evaluation of the Chinese Counseling Competencies Scale-Revised - Xia, Wei; Li, William Ho Cheung; Liang, Tingna; Luo, Yuanhui; Ho, Laurie Long Kwan; Cheung, Ankie Tan; Song, Peige (Frontiers in Psychology, 2021)
Objectives: This study conducted a linguistic and psychometric evaluation of the Chinese Counseling Competencies Scale-Revised (CCS-R). Methods: The Chinese CCS-R was created from the original English version using a standard forward-backward translation process. The psychometric properties of the Chinese CCS-R were examined in a cohort of 208 counselors-in-training by two independent raters. Fifty-three counselors-in-training were asked to undergo another counseling performance evaluation for the test-retest. The confirmatory factor analysis (CFA) was conducted for the Chinese CCS-R, followed by internal consistency, test-retest reliability, inter-rater reliability, convergent validity, and concurrent validity. Results: The results of the CFA supported the factorial validity of the Chinese CCS-R, with adequate construct replicability. The scale had a McDonald’s omega of .876, and intraclass correlation coefficients of .63 and .90 for test-retest reliability and inter-rater reliability, respectively. Significantly positive correlations were observed between the Chinese CCS-R score and scores of performance checklist (Pearson’s γ = .781), indicating a large convergent validity, and knowledge on drug abuse (Pearson’s γ = .833), indicating a moderate concurrent validity. Conclusion: The results support that the Chinese CCS-R is a valid and reliable measure of the counseling competencies. Practice implication: The CCS-R provides trainers with a reliable tool to evaluate counseling students’ competencies and to facilitate discussions with trainees about their areas for growth.